2009
DOI: 10.1080/08860220802546321
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Pentoxifylline Treatment on Gentamicin-Induced Nephrotoxicity in Rats

Abstract: Gentamicin (GM) is a widely used antibiotic against serious and life-threatening infections, but its usefulness is limited by the development of nephrotoxicity. Thus, the present study was undertaken to determine if pentoxifylline could protect the kidney in this experimental model. Thirty male Wistar rats were used. The animals were divided into three groups, each with 10 animals. The GM group of animals was treated daily with gentamicin in a dose of 100 mg/kg for eight days. The GMP group of animals was trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 45 publications
4
17
0
Order By: Relevance
“…On the other hand, Stojiljkovic et al [30] and Ozer et al [31] reported protective effects of pentoxifylline on aminoglycoside-induced nephrotoxicity, as assessed by serum creatinine and urea and histological analysis. It is conceivable that the mechanisms of protection provided by pentoxifylline against nephrotoxicity would not be operative in the pathogenesis of ischemia-induced renal injury.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Stojiljkovic et al [30] and Ozer et al [31] reported protective effects of pentoxifylline on aminoglycoside-induced nephrotoxicity, as assessed by serum creatinine and urea and histological analysis. It is conceivable that the mechanisms of protection provided by pentoxifylline against nephrotoxicity would not be operative in the pathogenesis of ischemia-induced renal injury.…”
Section: Discussionmentioning
confidence: 99%
“…27 Moreover, many studies have shown the beneficial effects of PTX in diabetic or nondiabetic kidney disease. It has been reported that PTX could provide an ameliorative effect against gentamicin, 9 cisplatin, 28 glycerol 29 and cyclosporine-induced nephrotoxicity. 30 In addition, PTX has shown beneficial effects in experimental models of DN and remnant kidney, with a reduction in renal hypertrophy, renal disease progression and urinary albumin excretion, 31 whereas clinical trials have demonstrated that PTF reduces clinical markers of glomerular and tubulointerstitial injury in diabetic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…8 In addition, it has been used as an antioxidant in order to heal damage in several tissues. 9 Previous studies reported that PTX ameliorates the clinical markers of glomerular and tubulointerstitial injury in diabetic patients. 10 In addition, recently reported studies indicate that PTX may decrease proteinuria.…”
Section: Introductionmentioning
confidence: 99%
“…Gentamicin nephropathy models have been more extensively studied, using molecules including fish oil, 4 pentoxifylline, 5 green tea, 6 caffeic acid phenyl ester (CAPE), 7 vitamin E and vitamin C, 8 and GSPE, 11 (a) (A) and so on. The AK nephropathy model has been used in fewer studies, but the effects of antioxidant molecules including CAPE, 3 N-acetylcysteine (NAC), 9 melatonin, 22 and pentoxifylline 10 have been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…4 Several experimental studies have been conducted in order to find a way to reduce AG-induced toxicity, and the effects of antioxidant molecules on reducing oxidative damage have been investigated in most of these studies. [3][4][5][6][7][8][9][10][11] It has been demonstrated that oxidative damage can be partially reduced by these drugs. However, there are as yet no molecules approved as an effective method to prevent AG nephropathy in clinical practice.…”
Section: Introductionmentioning
confidence: 99%